Light-induced optical absorption in the garnet Ca3Mn2Ge3O12 - Bedarev, V. A.; Gnatchenko, S. L.; Rupp, R. A.; Sugg, B. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1998)
Light-induced change in the optical absorption of the garnet Ca3Mn2Ge3O12 has been found. The magnitude of the light-induced optical absorption does not depend on the polarization state of the exciting illumination. The effect persists for a long time at low temperatures and can be attributed to light-induced generation or redistribution of Mn 4+ ions in the crystal.